Surgical excision with paramedian forehead flap reconstruction in recurrent basal cell carcinoma of the nose - Nathan Aditya Willyanto; Samsul Huda (Intisari Sains Medis, 2021)
Background:  Basal cell carcinoma (BCC) is the most common malignancy worldwide, especially in fair-skinned people. Along with squamous cell carcinoma (SCC), these malignancies are grouped as non-melanoma skin cancer (NMSC). The nose is a common site for BCC because it is exposed to the sun. The rates of recurrence are variable in the literature, between 10% and 67%. The ideal surgical treatment for BCC is complete tumor removal with safety margins. Wide excision of the BCC will leave the nose with a soft tissue defect and sometimes part of cartilage or skeleton, which requires nasal reconstruction.Case presentation: An 80-year-old female was admitted to the General Surgery Department of Soebandi General Hospital Jember presenting with ulceration on the right side of her nose 4 months before admission. The patient had a previous history of surgical excision on the nose 15 years ago on the nose's left side.Conclusion: Recurrent cases of BCC are still the main issue in treating BCC. Wide excision of the BCC will leave the nose with a soft tissue defect, which requires nasal reconstruction. The paramedian forehead flap is recommended for defect closure in nasal reconstruction.